Elements of civil engineering:(basic civil engineeing) - Agor, R (Khanna Publishers, 2015)
Elements of civil engineering:(basic civil engineeing) / Agor, R. -- New Delhi: Khanna Publishers, 2015 624 Ag275e6 6th ed. No. of Copies : 1